Serial measurements of SIRS criteria to identify unique phenotypes of sepsis: A Microbiologic Approach - Harman S Gill; Phuong H Nguyen; Jada M English; Kayla A Fay; Elisha Fleig Yin MPAS; Jaskirat Kaur Gill; Todd D Morrell (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2023)
Introduction: The utility of serial scoring systems in identifying distinct sepsis phenotypes remains unknown. Methods: Eligible adults were classified into culture-positive (Cx+) and culture-negative (Cx-) groups alongside pre-defined culture subgroups. Average SIRS & SEP (novel scoring system) scores were calculated at t = 0 and hours 3,6,12 & 24 before and after t = 0. The primary outcome was a difference in SIRS/SEP scores amongst those that were Cx+ or Cx- at any time point. Secondary outcomes were comparing total and component SIRS/SEP scores in microbiologic subgroups over serial time points.  Results: 4,701 Cx+ and 3254 Cx- patients met eligibility criteria. Statistically significant differences were seen in the average SIRS score between Cx + and Cx- groups at hours six (Cx+ 1.40+1.04 vs Cx- 1.35+1.01) & 12 (Cx+ 0.95+0.95 vs Cx- 0.90+0.90) after t = 0. The hematologic, urologic, and neurologic subgroups had significant differences at numerous time points before and after T = 0. Similar findings were observed with the SEP scores. Cx+ and Cx- groups (including subgroups) consistently doubled both SIRS/SEP scores before t = 0 with an eventual return to baseline values after T = 0 but at different gradients.  Conclusion: Significant differences in SIRS/SEP scores were seen in Cx+ & Cx- patients at sequential time points. This microbiologic approach in homogenous culture cohorts has the potential to identify distinct phenotypes of sepsis efficiently and practically. Consistent increases in SIRS/SEP scores before t = 0 and sequential decreases after t = 0 may allow for early detection, intervention, and provision for real-time monitoring of therapeutic responses in patients with concerns for sepsis.